(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the newly reorganized energy industry, determining how to divide up system losses between suppliers and end users is a complex issue. Given the importance of DGs in the new energy market structure, it is crucial that radial distribution networks with DGs properly allocate losses to both customers and generators. New loss allocation mechanism is presented in this study for radial distribution networks with DGs. Losses are divided up based on how the radial distribution network’s sink nodes and distributed generators (DGs) are set up. There are three separate stages to the algorithm used in this procedure. In the first stage, power loss is apportioned to the linked loads of the various source nodes. The next step accounts for the findings from this step by assigning the overall power loss to the DGs. At this point, power losses are assigned to individual nodes, beginning with sink nodes, and then normalized to account for them. This paper describes a method for equitably sharing out the costs associated with power flow losses in radial medium-voltage distribution networks powered by decentralized power plants. Using a genetic algorithm, we approximate the voltage at each of the 69 nodes in the distribution network and then compare our results to those obtained using the more traditional method.